SUPPLEMENTARY MATERIALS for Tools and considerations for mitochondrial haplogroup assignment - Sturk-Andreaggi, Kimberly (Uppsala University, 2022)
Supplemental tables associated with the "Tools and considerations for mitochondrial haplogroup assignment" manuscript. This study compared three haplogrouping tools and their ability to provide proper guidance based on the predicted phylogeny.

The dataset was originally published in DiVA and moved to SND in 2024.
SUPPLEMENTARY MATERIALS for Tools and considerations for mitochondrial haplogroup assignment
Keywords: Biology with Specialisation in Human Evolution and Genetics; Biologi med inriktning mot människans evolution och genetik; Biology with specialization in Molecular Biology; Biologi med inriktning mot molekylärbiologi; Genetics and Genomics; Genetik och genomik; Evolutionary Biology; Evolutionsbiologi; Forensic Science; Rättsmedicin